Identifikace determinantů přímých zahraničních investic v České republice - Vávrová, Daniela; Linhartová, Veronika (Univerzita Pardubice, 2018)
The issue of foreign direct investment is becoming an increasingly discussed topic in terms of possibilities of influencing their volume and their benefits for the national economy as well. Foreign direct investment can have a numerous impact on the host economy. It can influence the labor market, increase competitiveness, bring new management practices, know-how, innovation or interconnection of national economies. Investments can also have negative impacts on the national economy such as crowding out domestic businesses or inequality of investment inflows into different industries. The aim of the paper is based on empirical studies define the possible factors influencing the inflow of foreign direct investment into the country and identify the specific factors influencing the inflow of foreign direct investment into the Czech Republic. Using multiple regression analysis, the Expenditure on science and research, Gross domestic product, Corporation tax, and the Corruption perception index were identified as significant factors influencing foreign direct investment in the Czech Republic.
The identification of foreign direct investment´s determinants in the Czech republic
Keywords: foreign direct investment (FDI); inflows of FDI; determinants of FDI; regression analysis; Czech republic; D73; E2; F21